Graph the system of equations below on a piece of paper. What is the solution?
y = x – 1
y = 3x + 1

 

A. (2, 1)
 

B. (1, –2)
 

C. (–1, –1)
 

D. (–1, –2)

Respuesta :

Attached a solution and showed work.
Ver imagen Аноним

Answer:

Option D is correct

Solution = (-1, -2)

Step-by-step explanation:

Given the equation:

y = x – 1               ....[1]

y = 3x + 1            ....[2]

Equate equation [1] and [2] to solve for x.

[tex]x-1=3x+1[/tex]

Subtract x from both sides we have;

[tex]-1=2x+1[/tex]

Subtract 1 from both sides we have;

[tex]-2=2x[/tex]

Divide both sides by 2 we have;

x = -1

Substitute the value of x = -1 in [1] we have;

y=-1-1 = -2

Graphically:

Graph the system of equations as shown below.

The intersection point of these lines is the solution for the given system of equation

⇒ (-1, -2)

Therefore, the solution for the given system of equation is, (-1, -2)

Ver imagen OrethaWilkison